Exploring the relationship between environmentally related taxes and inequality in income sources An empirical cross-country analysis - Oueslati, Walid (OECD Publishing, 2016)
This paper presents the first empirical analysis of the macroeconomic relationship between environmentally related taxes and inequality in income sources. The analysis also investigates whether this relationship differs between countries which have implemented environmental tax reforms (ETRs) and ones which have not. Following earlier empirical literature, income inequality is measured by the disposable-income-based Gini coefficient. The analysis is based on a panel of all 34 OECD countries spanning the period from 1995 to 2011. Information about the implementation of ETRS in the examined period is collected through a review of relevant academic and policy literature. Empirical results from econometric models reveal that, on average, there is no statistically significant relationship between the overall share of environmentally related tax revenues in GDP and inequality in income sources. However, the relationship varies with the taxed activity under consideration and the existence of an explicit mechanism to redistribute environmentally related tax revenues. In countries where such mechanisms are absent, energy tax revenues (% of GDP) are shown to have a positive, although modest, relationship with income inequality. In contrast, in countries where energy tax revenues are, at least partially, used to reduce tax burden on income and labour, there is a negative relationship between energy taxes and inequality in income sources. On the contrary, no significant relationship is identified between motor vehicle and other transport tax revenues and income inequality, while revenues from other environmentally related taxes, such as waste and air pollution taxes, are negatively associated with income inequality, regardless of the existence of an explicit revenue recycling mechanism
Keywords: Environment